AMPK is essential for IL-10 expression and for maintaining balance between inflammatory and cytoprotective signaling - Guragain, Diwakar; Gurung, Pallavi; Chang, Jae-Hoon; Katila, Nikita; Chang, Hyeun Wook; Jeong, Byeong-Seon; Choi, Dong-Young; Kim, Jung-Ae (Biochimica et biophysica acta. General subjects, 2020)
AMP-activated protein kinase (AMPK) exerts its anti-inflammatory effects by suppressing redox-sensitive nuclear factor kappa B (NF-κB) and pro-inflammatory cytokines including TNF-α. However, it is unclear whether AMPK regulates anti-inflammatory cytokine expressions in the presence of oxidative stress-induced inflammation. We sought to elucidate the mechanisms whereby AMPK regulates inflammatory cytokine expressions under NADPH oxidase (NOX)-induced oxidative stress. HT-29 human colonic epithelial cells transfected with AMPKα shRNA and mouse models with AMPKα knocked out in epithelial cells (AMPKαfl/fl-Vil-Cre) or macrophages (AMPKαfl/fl-Lyz2-Cre) were used to examine the effects of AMPK and NOX on signaling pathways and cytokine expressions. In HT-29 cells, 5-hydroxytryptamine (5-HT)-induced NOX activity was enhanced by AMPKα silencing, and resulted in inflammatory cell death. AMPKα deletion specific for colon epithelial cells (AMPKαfl/fl-Vil-Cre) or macrophages (AMPKαfl/fl-Lyz2-Cre) intensified 5-HT- or dextran sulfate sodium (DSS)-induced upregulations of NOX2, TNF-α, and IL-6, but completely abolished basal and 5-HT- or DSS-induced upregulation of IL-10 in colon epithelium. Furthermore, 5-HT- and DSS-induced changes were accompanied by marked upregulations of increased inflammatory signaling pathways linked to NF-κB, AP-1, and STAT3 transcription factors, and to GATA, a cell fate-directing signaling. In addition, AMPKα deletion significantly fortified 5-HT- or DSS-induced downregulations of cytoprotective signaling pathways (Nrf2, HIF-1α, and KLF4). Basal AMPKα maintains an anti-inflammatory state by inhibiting NOX, balancing pro−/anti-inflammatory signaling pathways, and directing IL-10 production. When these regulatory roles of AMPK are diminished by oxidative stress, colon epithelium undergoes inflammation despite IL-10 production. [Display omitted] •Basal AMPKα maintains an anti-inflammatory state by inhibiting NOX.•AMPKα activity is inhibited by NOX2-mediated oxidative stress.•AMPKα deletion induces epithelial pyroptosis under oxidative stress.•AMPKα is essentially required for IL-10 expression.•AMPKα modulates crosstalk between Nrf2 and NF-κB in response to oxidative stress.